The Control Strategies for Information Asymmetry Problems Among Investing Institutions, Investors, and Entrepreneurs in Venture Capital - Du, Peng; Shu, Hong; Xia, Zhuqing (Frontiers in Psychology, 2020)
To analyze the problem of information asymmetry between investment institutions, investors, and entrepreneurs, thereby protecting the interests of all parties and ensuring the income under high risks, some companies listed on Shanghai Stock Exchange and Shenzhen Stock Exchange are taken as research samples. First, the relations between investment institutions, investors, and entrepreneurs, as well as the causes and solutions of information asymmetry in venture capital, are analyzed. Second, based on the residual model, a model that analyzes the information asymmetry and investment efficiency of the enterprise is built. Finally, through two cases, the relation between the information asymmetry and the investment rate is revealed. The research results show that from 2014 to 2018, the investment level of companies listed on the Shanghai Stock Exchange and Shenzhen Stock Exchange was below 7.69%; the investment levels of different companies varied greatly, with significant differences in the development situations. Besides, information asymmetry is significantly related to investment efficiency. The corresponding regression coefficient is 0.0119. The larger the enterprise is, the higher the investment efficiency will be. The case analysis shows that it is important to understand and seize the market, and the information asymmetry between the actual environment and the investment environment is more serious. To deal with these issues, material incentives, reputation incentives, control incentives, and stock option incentives are substantive measures that can be taken, which are of great significance for improving the decision-making level of investors and investment institutions and reducing the investment risk of investors and entrepreneurs.